Professional Zakat and Social Transformation: an Analysis of The Economic Empowerment Policy of The Baitul Maal Foundation of Bank Rakyat Indonesia (YBM BRI) - Hamid, Ahmad Munir; Arifin, Sirajul; Ahmed, Ishfaq (IKONOMIKA, 2024)
This study analyzes the role of Professional Zakat in social transformation through the economic empowerment policy of the Baitul Maal Foundation of Bank Rakyat Indonesia (YBM BRI). The research method uses a qualitative approach with data collection techniques through interviews and documentation studies. The results showed that YBM BRI has a strategic role in community economic empowerment through professional zakat. Through economic programs supported by zakat funds, YBM BRI has succeeded in providing training, business capital assistance, and coaching to the community to improve their economic independence. Policy analysis shows the importance of synergy between YBM BRI, the government, and the private sector in creating significant social impact. The implication of this research is the importance of continuing to increase the role of professional zakat in social transformation and inclusive economic development.